And your question is? If you just want to know how to solve this system, you only need to substitute one equation into the other and solve for the remaining unknown.

y=3x (equation 2), so plug it into equation 1

7x-2y=1

7x-2(3x)=1

7x-6x=1

x=1

from equation 2 then, you know y=3x=3

Posted on Oct 05, 2010

Hi,

a 6ya expert can help you resolve that issue over the phone in a minute or two.

best thing about this new service is that you are never placed on hold and get to talk to real repairmen in the US.

the service is completely free and covers almost anything you can think of (from cars to computers, handyman, and even drones).

click here to download the app (for users in the US for now) and get all the help you need.

goodluck!

Posted on Jan 02, 2017

y = x+1

y = (4) + 1

y = 5

y = x + 1

y = (-4) + 1

y = -3

2y - 2 = 2x

2y - 2 = 2 (4)

2y - 2 = 8

2y - 2 + 2 = 8 + 2

2y = 10

2y/2 = 10/2

y = 5

2y - 2 = 2(-4)

2y - 2 = -8

2y -2 + 2 = -8 + 2

2y = -6

2y / 2 = -6 /2

y = -3

The results are the same, implying that they are the same line.

Why?

2y - 2 = 2x

2y - 2 + 2 = 2x + 2

2y = 2x + 2

divide everything by 2

y = x + 1

Good luck,

Paul

y = (4) + 1

y = 5

y = x + 1

y = (-4) + 1

y = -3

2y - 2 = 2x

2y - 2 = 2 (4)

2y - 2 = 8

2y - 2 + 2 = 8 + 2

2y = 10

2y/2 = 10/2

y = 5

2y - 2 = 2(-4)

2y - 2 = -8

2y -2 + 2 = -8 + 2

2y = -6

2y / 2 = -6 /2

y = -3

The results are the same, implying that they are the same line.

Why?

2y - 2 = 2x

2y - 2 + 2 = 2x + 2

2y = 2x + 2

divide everything by 2

y = x + 1

Good luck,

Paul

Feb 07, 2017 | The Office Equipment & Supplies

Two equations:

x = first number

y = second number

2x - y = -1

y = 1 + 2x

2y + 3x = 9

2(1 + 2x) + 3x = 9

2 + 7x = 9

7x = 7

**x = 1**

**y =** 2(1) + 1 =** 3**

x = first number

y = second number

2x - y = -1

y = 1 + 2x

2y + 3x = 9

2(1 + 2x) + 3x = 9

2 + 7x = 9

7x = 7

Oct 25, 2016 | Cars & Trucks

Both should work.

16x - 2y = 16

4x - 2y = -8

-----------------

12x = 24

x = 2

y = 8

2y=4x + 8

y = 2x + 4

16x - 2(2x + 4) = 16

16x - 4x -8 = 16

12x = 24

x = 2

y = 8

Good luck.

Paul

16x - 2y = 16

4x - 2y = -8

-----------------

12x = 24

x = 2

y = 8

2y=4x + 8

y = 2x + 4

16x - 2(2x + 4) = 16

16x - 4x -8 = 16

12x = 24

x = 2

y = 8

Good luck.

Paul

Oct 05, 2014 | Office Equipment & Supplies

There must be an error: one of the = signs in the first set of equalities must be + or - (probably + because = and + share the same key on the keyboard). Please do use words to formulate the question. No one is a mind reader.

Jan 15, 2014 | Televison & Video

(2x - 3y)(3x + 2y) = 2x*3x + 2x*2y - 3y*3x - 3y*2y

= 6x^2 + 4xy - 9xy - 6y^2

= 6x^2 - 5xy - 6y^2 You multiply each element in the first set of brackets by each element in the second set of brackets and then consolidate like terms and arrange them in sequence of powers, first x and then y. So:

2x by 3x = 6x squared

2x by 2y = 4xy

-3y by 3x = -9xy

-3y by 2y = 6y squared

6x squared -5xy + 6y squared

= 6x^2 + 4xy - 9xy - 6y^2

= 6x^2 - 5xy - 6y^2 You multiply each element in the first set of brackets by each element in the second set of brackets and then consolidate like terms and arrange them in sequence of powers, first x and then y. So:

2x by 3x = 6x squared

2x by 2y = 4xy

-3y by 3x = -9xy

-3y by 2y = 6y squared

6x squared -5xy + 6y squared

Dec 04, 2010 | Yahoo Computers & Internet

4x+8y=20 || /4

x+2y=5

x=5-2y

-4x+2y=-30 || /2

-2x+y=-15

-2(5-2y)+y=-15

-10+4y+y=-15

5y=-5

y=-1

x=5-2y || y=-1

x=5-2(-1)

x=5+2

x=7

x+2y=5

x=5-2y

-4x+2y=-30 || /2

-2x+y=-15

-2(5-2y)+y=-15

-10+4y+y=-15

5y=-5

y=-1

x=5-2y || y=-1

x=5-2(-1)

x=5+2

x=7

Mar 10, 2009 | Bagatrix Algebra Solved! 2005 (105101) for...

x=3, y=1.5

Feb 12, 2009 | Bagatrix Algebra Solved! 2005 (105101) for...

Hi joanmae jmeh;

You can add these equations just like you would numbers

3x + 2y = 7

5x - 2y = 1

-----------------------

8x =8

x=1

Now plug x = 1 back into either equation and you can solve for y

Y = 2

When you add the 2 equations together the +2y and the -2y cancel

out

Hope this helps Loringh Please leave a rating for me Thks

You can add these equations just like you would numbers

3x + 2y = 7

5x - 2y = 1

-----------------------

8x =8

x=1

Now plug x = 1 back into either equation and you can solve for y

Y = 2

When you add the 2 equations together the +2y and the -2y cancel

out

Hope this helps Loringh Please leave a rating for me Thks

Dec 01, 2008 | Bagatrix Algebra Solved! 2005 (105101) for...

Hello,

This calculator cannot handle symbolic algebra.

Use the rules to simplify the expressions: Get rid of the parentheses using distributivity od multiplication with respect to addition; group similar terms (terms with x, terms without x).

Hope it helps.

This calculator cannot handle symbolic algebra.

Use the rules to simplify the expressions: Get rid of the parentheses using distributivity od multiplication with respect to addition; group similar terms (terms with x, terms without x).

Hope it helps.

May 07, 2008 | Casio FX-115ES Scientific Calculator

Sep 22, 2017 | Computers & Internet

174 people viewed this question

Usually answered in minutes!

×